Myth and reality of the soviet gold policy - Siegfried G. Schoppe (Intereconomics, 1978)
The Soviet Union has good prospects of becoming the dominant supplier of gold in the world, for its own mining reserves are large and the deposits in the Western world are nearing exhaustion. This need not however — as is shown in the following article — give rise to excessive fears in the West as the interests of the Soviet Union are pointing in the same direction as those of the West.
Keywords: 330; Gold Market